Review of the artificial intelligence act (De Legibus - Law Journal, 2025)
The Artificial Intelligence Act is implemented in phases, between February 2025 and August 2027; its provisions will apply in accordance with the potential risk level of AI systems to the protection of health, safety, and fundamental rights within the EU. In parallel, international cooperation is un- derway, led by the European Commission, to ensure compliance in the legal time frame.
Keywords: Artificial Intelligence Act; Regulation (EU) 2024/1689; Artificial Intelligence; Prohibited AI practices; Commission Guidelines; Generalpurpose AI.